A Feasibility Study on the Establishment of Duck House Farm in San Jose Rodriguez Montalban, Rizal (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Duck production is one of the most profitable livestock industries in the country mainly because of its egg which can be marketed through different channels. Some duck poultry farm uses anti-biotics in taking care and raising of ducks. Duck House Farm, however, will use the natural and traditional way of broiling of ducks to provide quality duck products free from manipulation of chemicals. The researchers conducted a survey in San Jose Rodriguez, Montalban Rizal. A total number of 100 respondents were surveyed about the proposed product, price, place and promotions acceptance. The type of questionnaire used by the researchers are scaling, multiple choice and dichotomous questions for residents and other businesses. The research survey results shows 41% of the respondents prefer dressed duck while 80% prefers duck meat cut into parts. One to twice a week, 60% of the respondents buy penoy/balut, 55% buy salted egg , 50% buy duck meat and 62% wants to purchase duck egg products. Respondents who prefer to buy duck products at the farm were at 11%, wet markets at 48% and suppliers at 41%. Twenty nine percent of the respondetns purchase 5-6 tray of balut/penoy per week, 31% purchase 5-6 tray of salted eggs a week while 37% purchase 5-6 traysof fresh eggs. Fifty four percent of the respondents buy duck meat for their business and 26% buy duck meat 3-4 times a week. All of the respondents prefer to buy in bulk with discounts. Regarding result for price of products, 39% agreed 10-11 pesos balut/penoy, 42% agreed to 10-11pesos of salted egg, 58% agreed 140-160pesos for a kilo of duck meat. Seventy three percent of the respondents agreed that the location is accessible. The researchers came up with a feasible business named Duck House Farm that offers balut, penoy, salted eggs, fresh eggs and meat from ducks and seminar/workshops related to its production. In deciding for price of the products and services, the researchers used cost-plus markup strategy while also considering the competitors price. The promotional activities of the business will use internet through facebook page and website. The business will also utilize print media including tarpaulin and flyers. The business has a walk-in store located at Lower Pinatubo St. San Jose Rodriguez Montalban. Rizal. This will provide productivity to farmers through profit and quality met products for the consumers from free-range ducks.
Keywords: feasibility study, duck meat, duck eggs, free-range